Increased open fracture complications following pediatric all-terrain vehicle accidents. Issue 10 (October 2022) - Torrez, Timothy W.; Hicks, Jimmy; Bonner, Vincent; Seidenstein, Alexandra H; McGwin, Gerald; Kothari, Ezan; Gilbert, Shawn R.
Highlights: Despite the abundance of literature on the dangers of ATVs to children, there is still a large number of ATV related open fractures at our institution. ATV related open fractures were associated with significantly higher rates of severe fracture types, Gustilo-Anderson II and III. Malunion, revision, and reoperation were more common in open fractures secondary to ATV accidents. The rate of infection in ATV and non-ATV related open fractures did not differ significantly. Abstract: Background: ATV (All-Terrain Vehicle) related open fractures are often high energy and may be highly contaminated. We asked whether they were more complicated than other open fractures in pediatric patients. Methods: A retrospective chart review was performed comparing ATV associated open fractures to open fractures sustained in non-ATV related accidents. 97 pediatric open fractures from 2015 to 2021 were identified based on ICD-10 codes. Of these fractures, 62 were non-ATV related and 35 were ATV related. Charts were reviewed to collect basic demographics, fracture pattern, Gustilo-Anderson classification, procedures performed, operative findings, and complications. Results: Our cohort was predominantly male (71% in the ATV group and 76% in the non-ATV group). White race was more common in both the ATV (28 (80%)) and non-ATV (50(78%)) groups. The distribution of AO/OTA fractures was significantly different ( p = 0.046), with humerus fractures being more common in the ATV group (8 (22%)) vs. non-ATV group (6 (9.3%)). The ATV group had a higher proportion of more severe type II and III open fractures with 77.1% ( n = 27), versus 56% ( n = 35) in the non-ATV group ( p = 0.020).. Revision and reoperation were more likely in the ATV group (16 (23%)) vs. the non-ATV group (12 (15%)), as was malunion (ATV group 3 (4.3%) Vs. non-ATV 0 (0%)). Conclusion: Open fractures resulting from ATV injuries tend to be more complex and have higher rates of revision and malunion. This information supports the large body of evidence on the dangers of ATVs to children and can help guide expectations of both clinicians and family members of patients presenting with these injuries.